Rumah Listrik Berbasis STEAM untuk Meningkatkan Keterampilan Berpikir Kritis dan Hasil Belajar Era Pandemi - Siska Yuniyati (Jurnal Didaktika Pendidikan Dasar, 2022)
The Covid-19 pandemic brings its own challenges in implementing the learning process. Constraints are encountered in learning electrical materials. Students cannot directly interact, explore, and construct knowledge as is usually done in the classroom. Teachers with all the available potential try to create learning conditions at home only and can achieve optimal learning goals. The objectives of this study are to 1) describe the STEAM-based electric house learning; 2) knowing the increase in critical thinking skills of students through STEAM-based electric house learning; 3) knowing the increase in student learning outcomes through STEAM-based electric houses learning. The subjects in this study were 16 grade VI students of SD Negeri Gentan 01, Bendosari District, Sukoharjo Regency, semester I of the 2020/2021 school year. This research is part of the best learning experiences in the Covid-19 pandemic era. The results of this study are: 1) a description of the STEAM-based electric house learning which is proven to be effective in increasing learning interest, motivation, and student activity in learning at home; 2) Increased critical thinking skills from the classical average score of 38,59 increased to 77,19 in the good category; 3) The increase in student learning outcomes from the average classical value before the application of STEAM-based electric houses learning was 69,06, increasing to 85, resulting in an increase of 15,94.